Value Chains in Agriculture - Ezekiel, R. (Indian Farming, 2015)
Prior to the implementation of the component -2 sub-projects, a few agricultural value chains existed in the country and they too were not well organized. They were mostly fragmented with no continuity as a value chain. Research organizations in the National Agricultural Research Systems worked independently and were not market driven. The NAIP sub-projects under component-2 helped establish an institutional mechanism to work with private partners in a consortium mode. As a result of this initiative several strong public-private partnerships were established, which helped in the development of many successful value chains with linkages to national and international markets. Successful and sustainable value chains developed under the NAIP include Agro-forestry, flowers, guava and mango, banana, custard apple, ginger, saffron, coconut, protected cultivation, sorghum, bioethanol, millets, linseed, prosopis, natural dyes, biomass, pashmina, meat, milk, dairy products, small pelagics, oysters, and tuna fish. It is hoped that these value chains will remain sustainable and will serve as an inspiration for the development of several more agricultural value chains in the future.